2020
DOI: 10.3389/fnagi.2020.00046
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Network Connectivity Patterns Associated With Normal Cognition at Old-Age, Local β-amyloid, Tau, and APOE4

Abstract: Background: Integrity of functional brain networks is closely associated with maintained cognitive performance at old age. Consistently, both carrier status of Apolipoprotein E ε4 allele (APOE4), and age-related aggregation of Alzheimer's disease (AD) pathology result in altered brain network connectivity. The posterior cingulate and precuneus (PCP) is a node of particular interest due to its role in crucial memory processes. Moreover, the PCP is subject to the early aggregation of AD pathology. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…Of the 4 studies applying seed-based connectivity, 2 indicated a positive association [20, 44] while 1 indicated a lower hippocampal FC in association with a higher τ burden in the inferior temporal cortex [21]. The last study mainly found a higher FC related to τ-PET covariance [17].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 4 studies applying seed-based connectivity, 2 indicated a positive association [20, 44] while 1 indicated a lower hippocampal FC in association with a higher τ burden in the inferior temporal cortex [21]. The last study mainly found a higher FC related to τ-PET covariance [17].…”
Section: Resultsmentioning
confidence: 99%
“…In the elderly with normal cognition, the connection between the occipital lobe and the posterior cingulate and precuneus is related to the tau protein, which may change in preclinical cognitive impairment (Quevenco et al, 2020). In patients with subjective cognitive decline, white matter damage across the frontal and occipital lobes was also found; this track is thought to be related to the gray matter damage such as the medial prefrontal cortex and posterior cingulate cortex in the early stage of AD (Luo et al, 2019).…”
Section: Similar Pattern Between the Obj-scd And Amci Groupsmentioning
confidence: 99%
“…ApoE is an important cholesterol carrier that supports lipid transport and repairs brain injury. The presence of ApoE ɛ4 alleles in bio-fluids is strictly associated with genetic risk factors involved in the emergence of cerebral amyloid angiopathy and age-related cognitive impairments that cause late onset of AD [111]. ApoE joins with a number of receptors on the cell surface to deliver lipids and hydrophobic Aβ-peptides, thus introducing toxicity, causing synaptic dysfunction, and resulting in the deterioration or death of neurons that finally leads to AD.…”
Section: Detection Of Ad Biomarkers In Biosamplesmentioning
confidence: 99%